Functional Characterisation of ClpP Mutations Conferring Resistance to Acyldepsipeptide Antibiotics in Firmicutes. (9th April 2020) - Malik, Imran T.; Pereira, Rebeca; Vielberg, Marie‐Theres; Mayer, Christian; Straetener, Jan; Thomy, Dhana; Famulla, Kirsten; Castro, Helena; Sass, Peter; Groll, Michael; Brötz‐Oesterhelt, Heike
Abstract: Acyldepsipeptide (ADEP) is an exploratory antibiotic with a novel mechanism of action. ClpP, the proteolytic core of the caseinolytic protease, is deregulated towards unrestrained proteolysis. Here, we report on the mechanism of ADEP resistance in Firmicutes. This bacterial phylum contains important pathogens that are relevant for potential ADEP therapy. For Staphylococcus aureus, Bacillus subtilis, enterococci and streptococci, spontaneous ADEP‐resistant mutants were selected in vitro at a rate of 10 −6 . All isolates carried mutations in clpP . All mutated S. aureus ClpP proteins characterised in this study were functionally impaired; this increased our understanding of the mode of operation of ClpP. For molecular insights, crystal structures of S. aureus ClpP bound to ADEP4 were determined. Well‐resolved N‐terminal domains in the apo structure allow the pore‐gating mechanism to be followed. The compilation of mutations presented here indicates residues relevant for ClpP function and suggests that ADEP resistance will occur at a lower rate during the infection process. Abstract : ClpP mutant analysis : ADEP antibiotics select ClpP out‐of‐function mutations in Firmicutes in vitro . Studying these ClpP defects provides a map of amino acids relevant for the function of ClpP. Several mutated ClpP proteins were purified, and their diverse impairments were characterised. A new S. aureus ClpP:ADEP co‐crystal structure shows an electrostatic network stabilising the N‐terminal gate.